2020
DOI: 10.1002/jpen.1956
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fat Globule Membrane Enhances Colonic–Mucus‐Barrier Function in a Rat Model of Short‐Bowel Syndrome

Abstract: Background Clinical research reveals that colon plays an important role in mitigating the effects of short‐bowel syndrome (SBS). Previously, we showed that the milk fat globule membrane (MFGM) had protective effects on gut barrier integrity in the rat SBS model. Here, we used the same rat model to investigate the effects of enteral MFGM supplementation on gut microbiota and colonic–mucus‐barrier function and its related mechanisms. Methods We randomly divided 24 male Sprague‐Dawley rats into 3 groups: Sham, SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The beneficial role of MFGM has already been explored in animals and adults. Studies on rodent models have proven the impact of MFGM on infection, inflammation, brain composition, and gut barrier integrity, as well as intestinal development [30][31][32][33][34]. Interestingly, pups fed control formula demonstrated delayed intestinal growth, while the MFGM supplementation normalized intestinal crypt depths, epithelial cell proliferation, make-up of intestinal epithelial cell subsets, and resembled the make-up of intestinal microbes of mother's milk-fed rats at the phylum level [34].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial role of MFGM has already been explored in animals and adults. Studies on rodent models have proven the impact of MFGM on infection, inflammation, brain composition, and gut barrier integrity, as well as intestinal development [30][31][32][33][34]. Interestingly, pups fed control formula demonstrated delayed intestinal growth, while the MFGM supplementation normalized intestinal crypt depths, epithelial cell proliferation, make-up of intestinal epithelial cell subsets, and resembled the make-up of intestinal microbes of mother's milk-fed rats at the phylum level [34].…”
Section: Discussionmentioning
confidence: 99%
“…Broad‐spectrum antibiotics successfully ameliorated liver inflammation and steatosis in SBS animals, 142 but reduced gut adaption 142,143 . Probiotics and prebiotics (Table 2) improved gut adaption and gut barrier function in SBS animals and patients in most studies 144‐153 with several showed no significant improvement 154,155 ; but many probiotics used in these studies encode bsh genes, such as Lactobacillus johnsonii and Bifidobacterium breve . Probiotics with high BSH activity increase bile acid deconjugation, decrease bile acid and lipid absorption, downregulate FXR signals and increase hepatic synthesis of bile acids and lipids 156,157 ; in IF, these effects could aggravate bile acid and lipid dysmetabolism and cause liver cholestasis and steatosis.…”
Section: The Ba‐gm Axis and Clinical Management Of Ifaldmentioning
confidence: 99%
“…The MFGM enhanced the gut barrier function and lowered the intestinal permeability in a rat model of short bowel syndrome ( Yu et al, 2021 ). Regulation of the NLRP6 inflammasome pathway contributed to the improvement of gut dysbiosis.…”
Section: The Role Of Milk Fat Globule Membrane (Mfgm) In Infant Nutri...mentioning
confidence: 99%